Can't hold any more! a large survey on cycling subjective experience at the limit of effort - Pérez-Díaz, J. J.; Benítez, I.; Salas-Montoro, J. A.; Zabala, M.; Sanabria, D. (Psychology of Sport and Exercise, 2025)
Cyclists frequently experience task failure, an abrupt inability to maintain high-intensity effort, pushing both physiological and psychological boundaries. Although the physiological underpinnings of task failure are well-documented, the associated subjective and perceptual experiences remain underexplored. To address this gap, we surveyed 2818 licensed cyclists, gathering extensive data on the subjective aspects of reaching the point of exhaustion. Key findings indicate that physical cues, particularly muscle pain, are the most salient sensations perceived as cyclists approach their effort limit. A majority of cyclists (60.5 %) reported that task failure often occurs before reaching their absolute maximum perceived exertion, highlighting a potential psychological influence on cessation. The perception of task failure as voluntary versus involuntary varied significantly with age, cycling experience, and the use of performance monitoring devices (e.g., powermeters), with older/experienced cyclists tending towards perceiving it as more voluntary. Common strategies reported to prolong effort included self-talk, goal focus, and conscious breathing regulation. The study also revealed a common alteration in time perception, with the majority experiencing a slowing of time during maximal exertion. Collectively, these findings emphasize that task failure is a multifaceted phenomenon driven by an interplay of physiological states, psychological factors, and subjective perception. A deeper understanding of these experiential dynamics holds potential for developing training interventions aimed at improving effort management and enhancing endurance performance.